Hill an' gully ride Jamaica : Westmoreland (Kingston, Jamaica : Creative Productions [CPTC Ltd.], 2001)
Hill an' gully is a Creative Productions video primarily about the Jamaican people in the ordinary course of their lives, especially in rural areas - where they live, what they eat, the natural and historical features of their environment (rivers, waterfalls, caves, sinkholes, blue holes, fishing beaches, ruins, churches etc.). Business enterprises that are developing in their midst and how they cope with drought, pests, plant diseases, flood, rocky roads, long distance walking to schools and church, the marketing of their crops etc; the stories they have to tell about myths and legends (river maids and rolling calves), historical happenings (the Frome riots) and about famous Jamaican characters they came across or were told about. We meet centenarians, community stalwarts, returning residents, families, children and the ordinary citizen just trying to make ends meet.
Ninety (90) minutes.
Keywords: Westmoreland (Jamaica)